LONG-TERM EFFECTS OF ORLISTAT ON EATING BEHAVIOR OF OBESITY PATIENTS - E. V. Korneeva (Российский кардиологический журнал)
Aim. The assessment of the influence of long-term orlistat use on the eating behavior of obesity patients.Material and methods.   Totally 189 young patients studied with various grade of obesity, of those 107 women and 82 men at the age 18-44 y. o. Comparison group consisted of 34 healthy women and 31 healthy men (mean age — 39,21±0,46 y.). The anthropometric study performed, evaluation of food taking behavior, measurement of ghrelin level in the blood serum via ELISA method. Non-medication treatment (hypocaloric diet, physical exertion) was provided during 3 months. If no effect, then orlistat was prescribed 120 mg per os t. i.d. for 6-24 months.Results.   Among the studied patients, there were various types of eating behavior disorders found, mostly of emotiogenic and external types, nonbalanced of the food being taken. The decrease of body mass and mean value of WC was more prominent in patients with the III grade of obesity. Ghrelin level in the blood correlated with DMI and WC. The decrease of ghrelin in blood serum by from 10,4% in 6 months treatment to 46,3% in 24 months treatment witnessed sufficient saturation by the food if rational pattern of eating had been kept. After the end of treatment stability of following the rational pattern of food intake and healthy life style in the orlistat group less than 6 months was 59,5%, in 24 months — 97,8%.Conclusion. Medication type of treatment, especially orlistat usage, is recommended to obesity patients as supportive to life style modification. Serious decrease of bodyweight is possible for the patients with obesity if long-term following healthy lifestyle.